2015
DOI: 10.3390/ijerph120911241
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of G6PD and HSP90 Beta in Mice with Benzene Exposure Revealed by Serum Peptidome Analysis

Abstract: The small peptides representation of the original proteins are a valuable source of information that can be used as biomarkers involved in toxicity mechanism for chemical exposure. The aim of this study is to investigate serum peptide biomarkers of benzene exposure. C57BL/6 mice were enrolled into control group and benzene groups of 150 and 300 mg/kg/d Serum peptides were identified by mass spectrometry using an assisted laser desorption ionization/time of flight mass spectrometry (MS). Differential peptide sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We previously performed serum peptidome analysis and found that G6PD is overexpressed in benzene-exposed mice exhibiting hematopoietic toxicities compared with that in normal control mice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously performed serum peptidome analysis and found that G6PD is overexpressed in benzene-exposed mice exhibiting hematopoietic toxicities compared with that in normal control mice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…G6PD is overexpressed in the plasma of mice exposed to benzene [ 8 ] and implicated in the maintenance of GSH in providing protection from oxidative damage. Considering these phenomena, we hypothesized that G6PD overexpression in benzene-exposed mice is a protective mechanism activated in response to oxidative stress induced by benzene exposure.…”
Section: Introductionmentioning
confidence: 99%